RAISING GENDER AWARENESS OR ELIMINATING GENDER STEREOTYPES IN EDUCATION - Avazova Gulzoda Usmanovna; Elmurodova L. T. (Galaxy International Interdisciplinary Research Journal, 2021)
The history of gender stereotyping which has led to inequalities between men and women is long and complex and it is recognized that legislation, though crucial and positive actions alone do not necessarily achieve de facto gender equality. A conscious effort on the part of society to change attitudes and to accommodate difference is a prerequisite for an inclusive society. Education plays a central role in this process. Education occupy a unique position in society, and the role of the school is fundamental in promoting gender equality. By raising awareness, broadening horizons, confronting misinformation, expanding the knowledge base to include the scholarship of women as well as men, and offering new models of behavior, the school can be seen as an instrument for positive change.